2006
DOI: 10.1152/ajpregu.00505.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ETB receptors increases superoxide levels in sympathetic ganglia in vivo

Abstract: ) found that endothelin (ET) stimulated O 2 Ϫ production in sympathetic ganglion neurons in vitro by activating ETB receptors. The objective of the present study was to determine whether activation of ETB receptors in vivo elevates O 2 Ϫ levels in sympathetic ganglia. Because ET B receptor activation increases blood pressure, we also sought to determine whether alteration in O 2 Ϫ levels was a direct effect of ET B receptor activation on sympathetic ganglia or an indirect consequence of hypertension. Male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…The article by Cao et al, 5 published in this issue of Hypertension, is one of a series of articles from this group 6 -8 that describe NAD(P)H oxidase expression and regulation of ROS production in sympathetic neurons located in prevertebral sympathetic ganglia of normotensive and hypertensive (deoxycorticosterone acetate [DOCA]-salt) rats. The present results confirm earlier findings that Nox1, Nox2, Nox4, p22 phox , and p47 phox are expressed in sympathetic ganglia [7][8][9] and that NAD(P)H oxidase activity in these ganglia is increased in DOCA-salt hypertension. 7 Two important novel findings of this study are that Nox subunits are differentially expressed in sympathetic versus sensory dorsal root ganglia (DRGs) with Nox4 expression being low in DRGs and relatively high in sympathetic ganglia and that NAD(P)H oxidase activity is decreased in hypertensive DRGs, an effect opposite to that seen in sympathetic ganglia 5 (see Figure).…”
Section: Is Nad(p)h Oxidase Upregulated In the Peripheral Nervous Syssupporting
confidence: 93%
See 2 more Smart Citations
“…The article by Cao et al, 5 published in this issue of Hypertension, is one of a series of articles from this group 6 -8 that describe NAD(P)H oxidase expression and regulation of ROS production in sympathetic neurons located in prevertebral sympathetic ganglia of normotensive and hypertensive (deoxycorticosterone acetate [DOCA]-salt) rats. The present results confirm earlier findings that Nox1, Nox2, Nox4, p22 phox , and p47 phox are expressed in sympathetic ganglia [7][8][9] and that NAD(P)H oxidase activity in these ganglia is increased in DOCA-salt hypertension. 7 Two important novel findings of this study are that Nox subunits are differentially expressed in sympathetic versus sensory dorsal root ganglia (DRGs) with Nox4 expression being low in DRGs and relatively high in sympathetic ganglia and that NAD(P)H oxidase activity is decreased in hypertensive DRGs, an effect opposite to that seen in sympathetic ganglia 5 (see Figure).…”
Section: Is Nad(p)h Oxidase Upregulated In the Peripheral Nervous Syssupporting
confidence: 93%
“…8 Exposure of ganglia to phenylephrine in vitro did not increase superoxide. 8 Studies in my laboratory have recently demonstrated increases in NAD(P)H oxidase expression (Nox2, p22 phox , p47 phox , and p67 phox ) and superoxide in sympathetic ganglia of apolipoprotein E-deficient mice with hypercholesterolemia.…”
Section: Increased Arterial Pressurementioning
confidence: 94%
See 1 more Smart Citation
“…We showed recently that infusion of S6c into rats causes increased concentrations of reactive oxygen species in sympathetic ganglia, which might serve to facilitate ganglionic transmission and thereby sympathetic arterial vasoconstrictor activity. 18 The possibility of sympathetically mediated blood pressure responses via ET B R stimulation is supported by earlier work from Pollock et al 37 They demonstrated that acute infusion of S6c still causes pressor responses in rats lacking functional ET B R in all tissues except those containing dopamine-␤-hydroxylase (such as sympathetic neurons).…”
Section: Discussionmentioning
confidence: 90%
“…18 Antimicrobial prophylaxis and postoperative analgesia were achieved by administration of ticarcillinclavulanate (200 mg/kg IP) and enrofloxacin (5 mg/kg IP) and buprenorphine (0.05 mg/kg SC), respectively. Rats recovered from anesthesia, under close observation, on a heating pad.…”
Section: Surgical Methods: Standard Vascular Catheterizationmentioning
confidence: 99%